Deprivations, futures and the wrongness of killing - Marquis, D. (BMJ Group, 2001)
In my essay, Why abortion is immoral, I criticised discussions of the morality of abortion in which the crucial issue is whether fetuses are human beings or whether fetuses are persons. Both argument strategies are inadequate because they rely on indefensible assumptions. Why should being a human being or being a person make a moral difference? I argued that the correct account of the morality of abortion should be based upon a defensible account of why killing children and adults is wrong. I claimed that what makes killing us wrong is that our premature deaths deprive us of our futures of value, that is, the goods of life we would have experienced had we survived. This account of the wrongness of killing explains why killing is one of the worst of crimes and how killing greatly harms the victim. It coheres with the attitudes of those with cancer or HIV facing premature death. It explains why we believe it is wrong to kill infants (as personhood theories do not). It does not entail that it wrongs a human being to end her life if she is in persistent vegetative state or if her future must consist only of unbearable physical suffering and she wants to die (as sanctity of human life theories do not). This account of the wrongness of killing implies (with some defensible additional assumptions) that abortion is immoral because we were fetuses once and we know those fetuses had futures of value. Mark Brown claims that this potential future of value account is unsound because it implies that we have welfare rights to what we need to stay alive that most people would reject. I argue that Brown is incorrect in two ways: a welfare right to what we need to stay alive is not directly implied by my account and, in addition, most of us do believe that dependent human beings have substantial welfare rights to what they need to stay alive. Brown argues that depriving us of a future of value of which we have mental representations both is a better explanation of the wrongness of killing and does not imply that abortion is immoral. I reply that (a) if Brown's arguments against my view were sound, those arguments could be easily adapted to show that his view is unsound as well and (b) Brown's view is both ambiguous and unsound on any interpretation. The most popular class of pro-choice argument strategies appeals to the view that some or all fetuses lack either a mental state or function or a capacity for a mental state or function necessary for possession of the right to life. Desires, interests, sentience, various concepts, moral agency, and rationality have all been suggested as candidates for this crucial mental role. Brown's analysis is one member of this class of strategies. I believe that it is possible to show that none of these strategies is reasonable. However, there are so many of these strategies that the required argument demands something more like a book and less like a short essay. The argument of the following essay is a piece of this larger argument. Key Words: Abortion • future of value • Mark Brown • Don Marquis • the right to life • welfare rights